Novel index of arterial reflected waves, Arterial Velocity pulse Index, relates to muscle sympathetic nerve activity independent of Arterial Pressure volume Index in patients with hypertension. (25th November 2020) - Sugimoto, H; Murai, H; Hamaoka, T; Mukai, Y; Inoue, O; Okabe, Y; Tokuhisa, H; Takashima, S; Kato, T; Usui, S; Sakata, K; Talamura, M
Abstract: Background: Arterial reflected wave is determined by not only atherosclerosis but also sympathetic nerve activity. Recently, Arterial Velocity pulse Index (AVI), which is an index of arterial reflected waves, and Arterial Pressure volume Index (API), which is an index of volume of a conductive blood vessel, have been proposed as new index of arterial stiffness. However, it is unclear whether API and AVI would be associated with muscle sympathetic nerve activity (MSNA) in hypertensive subjects. Purpose: The purpose of this study was to evaluate the correlation between AVI, API and MSNA in hypertensive subjects. Method: 41 hypertensive patients and 40 non-hypertensive subjects were included in this study. We performed a cross-sectional, observational study. Hypertension (HT) was defined as systolic blood pressure (SBP) ≥140 mmHg, diastolic blood pressure (DBP) ≥90 mmHg or medical treatment for HT. AVI and API was measured by NAS-1000 (Nihon Koden, Japan). MSNA, central sympathetic outflow to peripheral muscle, was recorded directly from peroneal nerve. MSNA was expressed by burst frequency (bursts/minute) and burst incidence (bursts/100heartbeats). Blood pressure, heart rate and MSNA were recorded simultaneously. Results: Age, systolic and diastolic pressure were significantly higher in hypertensive patients compared to control (40±15 vs 61±13 years, p<0.001; 142±16 vs 113±9 mmHg, p<0.001; 81±14 vs 67±9 mmHg, p<0.001). MSNA and AVI were significantly augmented in hypertensive patients compared to control (34±11 vs. 23±6 bursts/min, p<0.05; 26±7 vs. 16±4, p<0.05). AVI was correlated with MSNA in each group (hypertension: r=0.59, P<0.001, non-hypertension: r=0.51, p<0.001). However, no correlation was shown between API and MSNA in each group (hypertension: r=0.22, p=0.15, non-hypertension: r=0.07, p=0.63). Multiple regression analysis also showed MSNA was significantly related with AVI but was not with API. Conclusion: Our finding showed that AVI relates to MSNA independent of API in patients with hypertension. It suggested that Novel index of arterial reflected waves, AVI, is helpful to estimate augmented SNA in hypertensive subjects regardless of volume of a conductive blood vessel. Funding Acknowledgement: Type of funding source: None